Using of Procalcitonin Level in Differentiation between Bacterial Vaginitis Due to Pathogenic Bacteria and Normal Flora - Eman Ghadhban Salih; Mohammed Ismael Dawood; Nihad Khalawe Tektook (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study conducted to view the role of PCT level in initial finding of bacterial vaginitis in pregnantwomen. A total of 150 deep vaginal swabs (100 pregnant women and 50 pregnant women as controlgroup) were collected from the beginning of February 2019 to the end of May 2019 from inpatients andoutpatients women attended to Al-Fallujah teaching hospital. Media were organized & purified according toproducer’s guidance. The ready media were utilized for segregation , definition of the viable enumeration, identifying & sensibility workout these media were achieved in the wake of being solidified. Swabs wasinoculated bacteriological agars for isolation of causative bacterial types . Blood samples collected by veinpuncture for determination of PCT by using ELISA technique. The study showed that that 57% of pregnantwomen have vaginal swab for culture as compared with 48 of the control group (non- pregnant women). Theresults demonstrated that, 54.39% of pathogenic bacteria isolated from vagina of pregnant women was G-vebacteria and 45.61% was G+ve bacteria. S. aureus represented the highest rate of pathogenic isolates 45.61%in cases (43.86%) while 29.17 of the control group were infected equally by E coli and K. pneumonia.Thehighest rate of antibiotic sensitivity toward S. aureus isolates was occurred in levofloxacin (88.46%) whileit was completely resistant to ampicillin and lincomycin, 94.11% of E. coli isolates was sensitive to each oflevofloxacin and cefotaxime and 100% resistant to lincomycin, 92.85% of Klebsiella isolates was sensitive toamoxicalve while it was 100% resistant to ampicillin, erythromycin and lincomycin. Procalcitonin level washighly elevated among pregnant ones followed by healthy ones (26.79±9.4 v.s 9.236±0.6 pg/ml) at P value<0.01. The highest mean of Procalcitoninlevel is found among pregnant women with pathogenic bacteriaisolates of HVS culture (30.15±9.84 pg/ml) and the lowest mean is recorded among pregnant women withnormal flora isolates (23.72±7.25 pg/ml).Conclusions: Serum PCT was highly elevated in pregnant womenwith vaginitis especially who diagnosed with pathogenic bacteria.